Keterkaitan Kebutuhan Manusia dan Pengelolaan Sumber Daya Alam dalam Mewujudkan Pembangunan Berkelanjutan di Bypas Bandara Internasional Lombok (BIL) Kabupaten Lombok Barat - Rahmayati; Sarjan (Mataram University, 2026)
The development of transportation corridors often triggers significant spatial transformations and directly affects the socio-ecological dynamics of a region. Over the past decade, the Bypass BIL area in West Lombok Regency has rapidly developed as a strategic corridor connecting economic activities, residential areas, and the Mandalika tourism destination. This development has increased human demand for accessibility and economic opportunities, while simultaneously exerting pressure on the capacity and quality of natural resources. This study aims to analyze the interrelationship between human needs and natural resource management in achieving sustainable development in the Bypass BIL area using the Driver–Pressure–State–Impact–Response (DPSIR) framework. The research was designed using a mixed-methods approach that integrates post-positivist and constructivist paradigms. Data were collected through remote sensing analysis, field observations, in-depth interviews, focus group discussions, and document and secondary data analysis. The results indicate that economic demands, tourism development, and spatial planning policies serve as the main driving forces that generate environmental pressures in the form of land-use conversion and ecosystem degradation. These pressures have led to declining environmental conditions and increased socio-economic vulnerability among local communities. This study highlights the importance of integrative, collaborative, and environmentally ethical policy responses to ensure that the development of transportation corridor areas proceeds in an equitable and sustainable manner.